2017
DOI: 10.1039/c7fo01171g
|View full text |Cite
|
Sign up to set email alerts
|

A new heteropolysaccharide from the seed husks ofPlantago asiaticaL. with its thermal and antioxidant properties

Abstract: A new heteropolysaccharide (PMH) with a molecular weight of 1.4 × 10 kDa was isolated from the seed husks of Plantago asiatica L. The monosaccharide composition of PMH was determined as glucose, xylose, arabinose, rhamnose, galactose and galacturonic acid with a molar ratio of 1.0 : 1.8 : 2.4 : 3.8 : 4.9 : 8.5. The backbone of PMH consisted of 1,4-β-d-GalpA with the side chains mainly composed of 1,3-α-d-Galp and 1,2-α-d-Galp which were attached to the O-3 of GlapA. The thermal analysis using the Flynn-Wall-Oz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…In the present study, we found that fermented ginseng polysaccharides show superior potency than nonfermented ginseng polysaccharides on antioxidant via enhancing the hydroxyl radical, superoxide anion scavenging ability, and total antioxidant capacity. Niu et al (2017) reported that the antioxidant ability may positively related to the content of uronic acid, which means high uronic acid content exhibited higher antioxidant capacity. So, we hypothesized that the antioxidant activity of FGP was improved due to the increasing of uronic acid.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we found that fermented ginseng polysaccharides show superior potency than nonfermented ginseng polysaccharides on antioxidant via enhancing the hydroxyl radical, superoxide anion scavenging ability, and total antioxidant capacity. Niu et al (2017) reported that the antioxidant ability may positively related to the content of uronic acid, which means high uronic acid content exhibited higher antioxidant capacity. So, we hypothesized that the antioxidant activity of FGP was improved due to the increasing of uronic acid.…”
Section: Discussionmentioning
confidence: 99%
“…seed have reported different results. For example, a new type of low molecular weight heteropolysaccharide was found in the seeds of P. asiatica , which was mainly composed of rhamnose, galactose, and galacturonic acid (similar to pectin) ( Niu et al, 2017 ), and a new polysaccharide was also found in psyllium husk, which was mainly composed of xylose, glucose, and rhamnose ( Patel, Tanna, Gupta, Mishra, & Jha, 2019 ). It is worth mentioning that in both studies, these polysaccharides were isolated from the ground seeds.…”
Section: Extraction Physicochemical Properties and Structural Featuresmentioning
confidence: 99%
“…Plantaginis Semen (PS) is a traditional Chinese herbal medicine with diuretic, anti-inflammatory, and immune regulation effects [5][6][7]. After extensive research, it was found that PS contains a variety of active components, such as polysaccharides, iridoids, triterpenes, flavonoids, and alkaloids, and many of these ingredients are verified to have certain effects on xanthine oxidase (XOD) activity and uric acid excretion [8,9]. Under the guidance of traditional Chinese medicine theory, PS is a diuretic drug, and it has the characteristics of mild drug and little side effects.…”
Section: Introductionmentioning
confidence: 99%